Peran OIC dalam Mendorong Pertumbuhan Ekonomi Negara-Negara Muslim - Hidayatul Kamariah (Jujurnal Publisher, 2025)
This study examines the role of the Organisation of Islamic Cooperation in promoting economic growth among Muslim countries through economic cooperation, trade integration, investment, and the development of Islamic economics. The research applies a qualitative method using a library research approach by collecting data from books, academic journals, official reports, and publications from institutions such as COMCEC, SESRIC, ICDT, and the Islamic Development Bank. The findings indicate that OIC has significantly contributed to increasing intra-OIC trade, encouraging investment cooperation, and supporting the development of the halal industry and Islamic finance sectors. In addition, OIC plays an important role in strengthening digital economic transformation and empowering small and medium enterprises in member countries. However, several challenges remain, including economic disparities, political instability, and limited infrastructure among member states. Overall, OIC has substantial potential to become a major economic force capable of improving the welfare and economic sustainability of Muslim countries globally.